CHILDREN'S RELIGIOUS RIGHTS IN THE INDONESIAN CONSTITUTION: UNDERSTANDING OF RELIGIOUS MODERATION EARLY IN FAMILY ENVIRONMENTS OF DIFFERENT RELIGIONS - Muhammad Aminuddin Shofi; Moh. Hadi Ismanto (Balai Penelitian dan Pengembangan Agama Jakarta, 2022)
Currently, the fulfilment of children's religious rights is not interpreted as a parent's need to introduce religion to their children, but rather as a requirement to cultivate religious moderation principles. This is a method of shielding youngsters from religious teachings that promote puritanical and extremist attitudes. The study focuses on how parents of different faiths fulfil their children's religious rights and how this relates to their understanding of religious moderation. The study was carried out as a field study utilizing a qualitative methodology that included interviews and documentation of data gathering methods. According to the findings of the study, the fulfilment of children's religious rights by parents of various religions is consistent with the child's constitutional right to religious freedom. Children are allowed to learn about, understand, and choose their religion. The fulfilment of children's religious rights in this way is in line with the religious moderation movement's essence, especially in terms of instilling the value of religious tolerance between religious communities.